2008
DOI: 10.1159/000141918
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Kallikrein-Kinin System on Prostate and Breast Tumour Angiogenesis

Abstract: Background/Aims: Angiogenesis is important for the growth and progression of cancer cells. There is some evidence that the kallikrein-kinin system (KKS) is involved in cancer and angiogenesis. The present study investigated the effect of increasing concentrations of prostate and breast tumour cell metabolites on the proliferation of cultured endothelial cells, their tissue kallikrein (TK) secretion and KKS expression. Methods: Expression of TK and kinin receptors was investigated by immunochemistry, and secret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 20 publications
0
13
2
Order By: Relevance
“…dMVECs and DU145 cells were cultured in endothelial basal medium (EBM-2) and Dulbecco's Modified Eagle's Medium (DMEM), respectively, as previously described 10 .…”
Section: Cell Culturementioning
confidence: 99%
See 2 more Smart Citations
“…dMVECs and DU145 cells were cultured in endothelial basal medium (EBM-2) and Dulbecco's Modified Eagle's Medium (DMEM), respectively, as previously described 10 .…”
Section: Cell Culturementioning
confidence: 99%
“…They later suggested that BK enhanced angiogenesis by promoting tumour vascular permeability 16 . More recently TK, B1R and B2R have been shown to be present in the membrane projections of both endothelial and prostate cancer cells in vitro 10 .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Tumour medium was supplemented further as previously described. 11 Only DMVECs between passages 4 and 12 were used for the challenge and co-culture models.…”
Section: Cell Culturementioning
confidence: 99%
“…11 Briefly, DMVECs were seeded onto 8-chamber glass slides (Iwaki Glass Co., Iwaki, Japan) at 2 x 10 3 cells/cm 2 . After 24 h, MCF-7 cells were added to each DMVEC chamber at 2 x 10 3 cells/cm 2 .…”
Section: Co-culture Modelmentioning
confidence: 99%